Hubungan Kekuatan Otot Lengan Dan Panjang Lengan Terhadap Keterampilan Servis Bawah Pada Olahraga Bola Voli Di SMA VIP Al Huda Kebumen - M Mualip (Journal on Education, 2025)
Physical education plays a crucial role in the physical and mental development of students, as well as in character building and social skills. This study aims to explore the relationship between arm muscle strength and arm length on underhand serve skills in volleyball among class X students at SMA VIP Al Huda Kebumen. Using a quantitative approach with a correlational design, this research involved 66 students randomly selected from a population of 80 students. Data were collected through measurements of arm muscle strength using push-up tests, arm length with a measuring tape, and underhand serve skills through the AAHPER accuracy serve test.The analysis results showed that all variables were normally and homogeneously distributed. The correlation between arm length and underhand serve skills showed a calculated r value of 0.783, while the correlation between arm muscle strength and underhand serve skills showed a calculated r value of 0.628. Both relationships were significant with p < 0.05. Additionally, the multiple correlation analysis between arm length and arm muscle strength on underhand serve skills showed a calculated r value of 0.394, which was also significant. These findings emphasize that increasing arm muscle strength and arm length can contribute to improving underhand serve skills, highlighting the importance of integrating structured training in physical education to enhance students' skill quality.